2001
DOI: 10.1148/radiol.2211001582
|View full text |Cite
|
Sign up to set email alerts
|

Localized Prostate Cancer: Effect of Hormone Deprivation Therapy Measured by Using Combined Three-dimensional1H MR Spectroscopy and MR Imaging: Clinicopathologic Case-controlled Study

Abstract: When performed within 4 months after initiating hormone deprivation therapy, combined MR imaging/3D MR spectroscopic imaging had the same accuracy in localizing prostate cancer as in nontreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 34 publications
1
71
0
2
Order By: Relevance
“…These initial studies suggested that MRSI could discriminate successful therapy (complete loss of prostatic metabolites) from residual disease. Subsequent studies have indicated that MRSI can also detect residual disease after unsuccessful hormone deprivation therapy (87,88) and radiation therapy (89). Figure 5 shows an example of a patient with biopsy-proven cancer in the left lobe, who had a PSA of 0.6 ng/ml at the time of the MRI/MRSI exam, which was almost 3 years after intensity modulated radiation therapy was administered.…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These initial studies suggested that MRSI could discriminate successful therapy (complete loss of prostatic metabolites) from residual disease. Subsequent studies have indicated that MRSI can also detect residual disease after unsuccessful hormone deprivation therapy (87,88) and radiation therapy (89). Figure 5 shows an example of a patient with biopsy-proven cancer in the left lobe, who had a PSA of 0.6 ng/ml at the time of the MRI/MRSI exam, which was almost 3 years after intensity modulated radiation therapy was administered.…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…Additionally, recovery of bilateral metabolic abnormalities consistent with biopsy findings prior to therapy was observed. Studies are currently under way to investigate the accuracy of MRI/MRSI in assessing the presence and spatial extent of prostate cancer after these therapies (87); the prognostic value of the time course to metabolic atrophy; the duration of undetectable metabolism; and the rate of metabolic recovery, particularly of cancer. The detection of residual cancer at an early stage following treatment, and the ability to monitor the time course of therapeutic response would allow earlier intervention with additional therapy and provide a more quantitative assessment of therapeutic efficacy.…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…8 mpMRI data are reliable only if acquired before androgen deprivation (hormone) therapy, as there is profound functional signal degradation after hormone therapy. [9][10][11] Our standard institutional practice for intermediate-and high-risk localized prostate cancer uses hormone therapy for 3-6 months prior to external beam radiotherapy, [12][13][14] so modelling a radiation boost to mpMRI-defined tumour nodules requires acquisition of functional data before hormone therapy to be registered with anatomical images obtained post hormone treatment and immediately prior to radiotherapy 15 in order to translate the tumour location to radiotherapy planning CT images. The aim of this planning study therefore was to demonstrate the use of a mpMRI-defined DIL to create a radiotherapy boost volume.…”
mentioning
confidence: 99%
“…Studies have shown that MRSI is able to discriminate residual or recurrent prostate cancer from benign and necrotic tissue after radiotherapy (Pickett et al, 2004;Roach et al, 2001), cryosurgery (Mueller-Lisse et al, 2001a;Parivar et al, 1996;Parivar and Kurhanewicz, 1998), and hormone deprivation therapy (Mueller-Lisse et al, 2001a, 2001b. Early detection of residual cancer with MRSI may allow early intervention with additional therapy.…”
Section: Mrsimentioning
confidence: 99%